Arctic driftwood proposal for durable carbon removal - Büntgen, Ulf; Oppenheimer, Clive; Trnka, Mirek; Kempf, Michael; Holman, Ian P.; Arosio, Tito; Bebchuk, Tatiana; Esper, Jan (Springer, 2026)
Various geoengineering approaches have been proposed for carbon dioxide (CO2) removal but their viability at scale remains unclear. Here, we consider the natural behaviour of driftwood, the warming-induced acceleration of sea-ice loss and tree growth, as well as the stability of cellulose in subfossil wood under cold-anoxic conditions, to introduce the concept of sinking timber from the boreal forest for durable CO2 sequestration at the deep Arctic Ocean floor.
Keywords: 37 Earth Sciences; 3709 Physical Geography and Environmental Geoscience; 31 Biological Sciences; 13 Climate Action